Adaptive coordinated leader–follower control of autonomous over-actuated electric vehicles. (December 2017) - Guo, Jinghua; Luo, Yugong; Li, Keqiang
In this paper, the leader–follower formation control problem of autonomous over-actuated electric vehicles on a highway is studied. As the autonomous over-actuated electric vehicles have the characteristics of non-linearities, external disturbances and strong coupling, a novel coordinated three-level control system is constructed to supervise the longitudinal and lateral motions of autonomous electric vehicles. Firstly, an adaptive terminal sliding high-level control algorithm is designed to compute a vector of total forces and torque of vehicles, and the stability of the high-level control system is proven via Lyapunov analysis where uniform ultimate boundedness of the closed-loop signals is guaranteed. Then, a pseudo-inverse control allocation algorithm, which can achieve fault tolerance and reconfiguration of the redundant tyre actuation system, is presented to generate the desired longitudinal and lateral tyre forces. Then, a separate low-level controller consisting of an inverse tyre model and two inner loops for each wheel is designed to achieve its desired forces. Finally, simulation results demonstrate that the proposed control system not only enhance the tracking performance, but also improve the stability and riding comfort of autonomous over-actuated electric vehicles in a platoon.